(3GdTGAs - (3YHO Gdedc Hf bQjH Hf Ydj Hf CUeY GdHGgdj, CHh SYjO GdCUeYj,J (B216 (3g` s ((3CMeO Hf ESeGYjd Hf eMeO JjehQ s)
(3ChdgG (B:s
(3CNHQfi GdTjN GdegPH CHh GdMSf Ydi SfI CQHY hNeSjf hNeS eFI bQCJ Ydi GdCUeYi(B: (3GdhbJ GdLjO ai GdTGA Cf JNdi SHYg GTgQ HYO hdGOgG , ajchf MedgG NeSI CTgQ s
(3BNQgG (B:s
(3hEPG cGfJ GdTGI efUhHI GdbQfjf bjd TGI fUHGA , hJjS CfUH hEPG XgQJ bQfGgG bHd XgQgG s
(3GdNW Hg edGeM GdNW GdaGQSis
(3HChdgG hba HNW GdfGSN SfI (B1322(3g`s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B162 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B187s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs